Phase angle is a predictor of overall 5-year survival after head and neck cancer surgery - Neyara dos Santos Oliveira; Marcelo Leandro Santana Cruz; Ramon Silva de Oliveira; Tércio Guimarães Reis; Márcio Campos Oliveira; José de Bessa Júnior (Brazilian Journal of Otorhinolaryngology)
Objective: To evaluate the ability of the variables Muscle Mass percentage (%MM), Body Fat percentage (%BF), Phase Angle (PhA), and Standardized Phase Angle (SPhA) to predict overall survival rates in individuals with surgically treated HNC. Methods: A prospective cohort study of surgically treated HNC patients was carried out between 2017 and 2022 at a cancer referral center in Feira de Santana, Bahia. All subjects were seen by an experienced dietitian the week before surgery. During this visit, patients had their sociodemographic and clinical data collected, as well as anthropometric measurements (weight and height) and BIA variables. In this study, postoperative overall 5-year survival was defined as the time in months between the date of surgery and the date of death, regardless of the cause of death. Patients were followed up after surgery until death. Results: Seventy-eight older adult patients were consecutively included. Patients had a median age of 65.5-years, were mostly men (83.3%), and most had low education levels (62.3%) and low household income, ranging from zero (19.2%) to the minimum wage (60.2%). They were mostly alcohol drinkers (91%) and tobacco smokers (87.2%). Glottic cancer was diagnosed in 48.7% of patients, with 44.8% of cases with stage-IV disease. Forty (51.2%) deaths were recorded in the follow-up period, with a median survival time of 39 months. Variables %MM, %BF, and SPhA were not significantly different between groups (alive vs. dead patients). PhA was considered an independent predictor of overall survival, with an accuracy of 69% (95% CI 0.57‒0.80). When comparing survival curves, patients with a preoperative PhA < 6.8° were more than twice as likely to die during follow-up (HR = 2.38; p =  0.02; 95% CI 1.14‒4.97). Conclusion: Out of the assessed BIA variables, preoperative PhA was considered a good predictor of overall survival after HNC surgery. Level of evidence: 3.